Development of microparticles and microparticulated tablets containing piperine - Aline Colling Schneider; Carlos Eduardo de Souza Brener; Natália de Freitas Daudt; Letícia Cruz; Cristiane de Bona da Silva (Universidade de São Paulo, 2023)
Abstract Piper nigrum (black pepper) is used in Indian traditional medicine and its main alkaloid, Piperine (PIP), presents antioxidant, antitumor and neuroprotective pharmacological properties. This substance is insoluble in aqueous media and can irritate the gastrointestinal tract. Aiming to avoid these inconvenient characteristics and enable PIP oral administration, this study suggested the PIP microencapsulation through the emulsion-solvent evaporation method and the preparation of microparticulated tablets by direct compression. An UV-spectroscopy method was validated to quantify PIP. Microparticles and microparticulated tablets were successfully obtained and the microparticles exhibited excellent flow. The scanning electron microscopy images showed that PIP microparticles were intact after compression. The in vitro release showed a controlled release of PIP from microparticles and PIP microparticles from tablets in comparison to PIP and PIP tablets. The release profiles of PIP microparticles and the microparticulated tablets were similar. Therefore, tablets containing PIP microparticles are promising multiparticulated dosage forms because a tablet allows microparticles administration and the intact ones promote a controlled release, decreasing its irritating potential on the mucosa.